Agreement between an automated video-based system and tethered system to measure instantaneous swimming velocity - Scott, M.; Elsworthy, N.; Brackley, V.; Elipot, M.; Kean, C. O. (Sports Biomechanics, 2024)
Successful performance in competitive swimming requires a swimmer to maximise propulsion and minimise drag, which can be assessed using instantaneous swimming velocity. Many systems exist to quantify velocity, and therefore, it is important to understand the agreement between systems. This study examined the agreement between an automated video-based system and a tethered system to measure instantaneous velocity. Twenty-two competitive swimmers (state level or higher) completed 25 m of each stroke at maximal intensity. The tethered speedometer was attached to the swimmer`s waist, while videos of each trial were recorded. The swimmer`s head was then automatically tracked using proprietary software, and instantaneous velocity was determined from each system. Bland-Altman plots showed good agreement between the two systems in backstroke (95% Limits of Agreement (LOA): -0.24-0.26 m.s-1) and freestyle (95% LOA: -0.36-0.38 m.s-1) but poorer agreement in butterfly (95% LOA: -0.51-0.53 m.s-1) and breaststroke (95% LOA: -0.88-0.92 m.s-1). The root mean square error was higher in butterfly (0.27 m.s-1) and breaststroke (0.46 m.s-1) compared to backstroke (0.13 m.s-1) and freestyle (0.19 m.s-1). Results demonstrated that the two systems are comparable for measuring instantaneous swimming velocity; however, larger discrepancies are evident for butterfly and breaststroke.